2021
DOI: 10.4070/kcj.2021.0027
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Dementia in Patients with Atrial Fibrillation

Abstract: Author's summary Atrial fibrillation (AF) has been associated with an increased risk of dementia. Although there does not appear to be solid evidence that any specific treatment prevents or delays AF-associated cognitive decline, evidence is accumulating regarding the possible treatment strategies for preventing dementia. In this review, we summarize the evidence linking AF to dementia and critically appraise the proposed treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Unfortunately, these drugs remain under administered in elderly patients with dementia, even in the presence of AF 43,44 . Other findings showed that more invasive treatment, such as catheter ablation, may be another optional treatment to reduce the burden of dementia in these patients, but in most of cases but it remains an invasive procedure with related risk especially in elderly subjects with serval comorbidities and a potential source of silent strokes and cognitive impairment 23,45 . From a pathophysiological perspective, dementia and AF seems to be linked by the appearance of micro embolic events as well as microinfarcts, as those observed in AD patients 24,46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, these drugs remain under administered in elderly patients with dementia, even in the presence of AF 43,44 . Other findings showed that more invasive treatment, such as catheter ablation, may be another optional treatment to reduce the burden of dementia in these patients, but in most of cases but it remains an invasive procedure with related risk especially in elderly subjects with serval comorbidities and a potential source of silent strokes and cognitive impairment 23,45 . From a pathophysiological perspective, dementia and AF seems to be linked by the appearance of micro embolic events as well as microinfarcts, as those observed in AD patients 24,46 .…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Other findings showed that more invasive treatment, such as catheter ablation, may be another optional treatment to reduce the burden of dementia in these patients, but in most of cases but it remains an invasive procedure with related risk especially in elderly subjects with serval comorbidities and a potential source of silent strokes and cognitive impairment. 23,45 From a pathophysiological T A B L E 3 (Continued) perspective, dementia and AF seems to be linked by the appearance of micro embolic events as well as microinfarcts, as those observed in AD patients. 24,46 Proinflammatory states are actively implicated in both the genesis and perpetuation of AF, as well as in the promotion of hypercoagulability and thrombus formation, predisposing to stroke.…”
Section: Discussionmentioning
confidence: 99%
“… 10) Integrated AF management controlling risk factors was also shown to be associated with a lower risk of dementia. 64) 65) 66) 67) …”
Section: Rhythm Control and Prevention Of Dementiamentioning
confidence: 99%
“…The effect of rhythm control treatment for AF on cognitive outcomes has been unclear. 67) 68) A sub-analysis of the AFFIRM trial reported no difference in cognitive function between treatment strategies of rate or rhythm control. 69) However, several observational investigations have suggested that AF ablation may improve cognitive function and reduce dementia risk.…”
Section: Rhythm Control and Prevention Of Dementiamentioning
confidence: 99%
“…However, recent research has indicated that there is a high prevalence of dementia in atrial fibrillation patients independent of age and past cerebrovascular accident (CVA). 2 , 3 Even after adjusting all possible confounding variables presence of AF confers a 2-to-3-fold increased risk of developing cognitive dysfunction and dementia. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%